Factors that influence Islamic work ethics among employees: A study at HIG Langkawi Holdings Sdn. Bhd. - Kamariah, Mohd Fisol (2016)
The purpose of this study was to review the factors that influence Islamic work ethics among the employees of Haji Ismail Group (HIG) Langkawi Holdings Sdn. Bhd. that located in Langkawi, Kedah. This study due to the lack of attention given regarding of the factors that influence the implementation of Islamic work ethics among employees especially in contexs of Malaysia’s environment. From this study, Islamic work ethics and it’s factors were measured it’s relationship in the implementation of Islamic work ethics among the employees and to identify the most dominant factor of Islamic work ethics among the employees. The data analysis was done by Statistical Package for Social Science (SPSS) version 21.0. The results showed a positive relationships between the perceived organizational support, Islamic education, person job fit and person organization fit with Islamic Work Ethics among employees. These positive relationships showing all these factors are significant as the factors of influencing employees to practice Islamic work ethics in their work routine. This study also found that the most dominant factor towards the implementation of the Islamic work ethics among employees is the Islamic education